The Cognitive-affective Distinction in Achievement Goal: The Development and Validation of the Achievement Questionnaire for Biology Learning - Cennet Elmas; Bahattin Deniz Altunoglu (International Council of Associations for Science Education, 2023)
K-8 science teacher candidates often struggle with the difficult learning tasks in multiple science courses in their teacher-training program. One of the major parts of these science courses is biology. Student learning in biology depends on their motivational and affective variables as much as their cognitive abilities. As one of the theories of motivation, the achievement goal theory seeks how individuals pursue academic study by focusing on mastery or performance goals. In addition to goal settings, achievement emotions also influence learners’ academic performance. The authors suggested a theoretical model integrating achievement emotions into the construct of achievement goal theory. The present study has potential provide more insight into individual differences in goal preferences. This model was examined with K-8 science teacher candidates (n = 581). To test the theoretical model, the “Achievement Goal Questionnaire for Biology Learning” (AGQ-BL) was devised. According to the theoretical model, the AGQ-BL consisted of six subscales which are Mastery Goals-(affective-cognitive), Performance Goals-Approach (Affective-Cognitive), and Performance Goals Avoidance-(affective-cognitive). The explanatory factor analysis (EFA) and confirmatory factor analysis (CFA) were utilized to verify the construct validity of the AGQ-BL. The results of EFA showed and CFA confirmed that the AGQ-BL was composed of six factors, as proposed by the theoretical framework. Internal consistency of the subscales of the AGQ-BL computed by Cronbach’s alpha revealed high reliability for each. This study empirically demonstrated the integration of cognitive and emotional goals in achievement settings regarding biology learning. Thus, it can be asserted achievement goals’ structure could have more predictive potential on affective and cognitive variables in biology education.
Keywords: achievement emotions; k-8 science teacher candidates; Science; Q; achievement goals; biology learning; Theory and practice of education; LB5-3640; 4. Education